2013
DOI: 10.3109/10826084.2013.841246
|View full text |Cite
|
Sign up to set email alerts
|

Is low BMI Associated with Specific Drug Use Among Injecting Drug Users?

Abstract: Body mass index (BMI) of a sample of people who regularly inject drugs (N = 781) was examined to gauge the impact of specific types of drug use. Cross-sectional interviews were undertaken in 2010 as part of a national monitoring program funded by the Australian Government. Latent class analysis identified three groups of drug users, with heroin users at 3.4 times the risk of being underweight compared with amphetamine users, and amphetamine users were at almost twice the odds of being obese compared with lower… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
13
1
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 40 publications
0
13
1
1
Order By: Relevance
“…We used latent class analysis (LCA) to derive empirical classes of polysubstance use profiles among the full sample (n = 2673) and test for measurement invariance by OST status using Mplus version 6 [20], similar to a previous IDRS study [21], and used full information maximum likelihood (FIML) to account for missing data [22] (for further information see Supporting information, Text S1). Each of the resulting classes was constructed as a dummy variable such that: (i) in analyses where the classes were dependent variables, each class could be predicted by the covariates using all the other classes combined as the reference group; and (ii) in analyses where the classes were independent variables, any number of classes could be excluded from the analyses to form a combined reference group, such that it was possible to identify specific classes which were associated with the outcomes when compared with many or all of the other classes (see Table 4).…”
Section: Discussionmentioning
confidence: 99%
“…We used latent class analysis (LCA) to derive empirical classes of polysubstance use profiles among the full sample (n = 2673) and test for measurement invariance by OST status using Mplus version 6 [20], similar to a previous IDRS study [21], and used full information maximum likelihood (FIML) to account for missing data [22] (for further information see Supporting information, Text S1). Each of the resulting classes was constructed as a dummy variable such that: (i) in analyses where the classes were dependent variables, each class could be predicted by the covariates using all the other classes combined as the reference group; and (ii) in analyses where the classes were independent variables, any number of classes could be excluded from the analyses to form a combined reference group, such that it was possible to identify specific classes which were associated with the outcomes when compared with many or all of the other classes (see Table 4).…”
Section: Discussionmentioning
confidence: 99%
“…MetS represents a complex pathophysiological condition that may develop in OUD patients [54][55][56][57] even independent of MAT, from increased caloric intake, decreased energy expenditure owing to reduced physical activity or a combination of both 8,21 . This assertion is however undermined by: (1) preponderance of studies reporting low body weight in short half-life opioid (e.g., heroin) abusers who are not on MAT agonist therapy [58][59][60][61] even in the face of glucoregulatory abnormalities [62][63][64] ; and (2) excessive BWG consistently noted in OUD patients following the initiation of methadone [65][66][67][68][69][70][71] and to a lesser degree buprenorphine 6,7,72 treatment. Nonetheless, the debate about the issue is still ongoing 73 with a number of reports on the opposite directionality of the metabolic responses 74,75 , including hemoglobin A1C level decreases in buprenorphine-maintained NIDDM patients 76 in conjunction with heightened insulin sensitivity in methadone-treated OUD patients 77 as well as hypoglycemia in patients receiving chronic analgesia with methadone 78 .…”
mentioning
confidence: 99%
“…Glutathione is the most abundant thiol containing intracellular molecule (11) and is converted to GSSG when oxidized. It has been reported that reduced glutathione is decreased and oxidized glutathione is increased in the saliva of the heroin addicts (12). Reduced glutathione is dominant in the intracellular environment.…”
Section: Discussionmentioning
confidence: 98%